Experimental Investigation of Electrochemical Capacitive Responses versus Pore Geometries through Artificial Nanotubes - Jianyou Dai; Minghao Xu; Zhangshanhao Li; Shuoxiang Liu; Yuyao Wang; Lei Shan; Xiaohong Wang; Sixing Xu (Micromachines, 2023)
Electrochemical supercapacitors have attracted significant attention due to their large capacity, high-power output, and long cycle life. However, despite extensive studies and advancements in developing highly porous electrode materials, little quantitative research on the impact of pore geometry on electrochemical responses has been conducted. This paper presents the first quantitative investigation of the relationship between electrochemical capacitive responses and pore geometries at the nanoscale. To achieve this, we constructed a uniform cylindrical pore array with controllable pore diameter and depth by using anodized aluminum oxide (AAO) to serve as a template and atomic layer deposition (ALD) technology for TiN conductive layer decoration. Our findings reveal that, at the nanoscale, increasing the specific surface area through pore diameter and depth does not proportionally increase the capacitive response, even at low scan rates. Meanwhile, we observe a critical pore parameter (170/5000 nm, diameter/depth), where the specific capacitance density and characteristic frequency dramatically decrease with a further increase in the pore aspect ratio. These results indicate that blindly pursuing the absolute specific surface area of the electrode material is not advisable. Instead, optimal pore geometry should be designed based on the desired operational conditions, and this work may serve as valuable guidance.